If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 6x = 3 Reorder the terms: 6x + y = 3 Solving 6x + y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 6x + y + -1y = 3 + -1y Combine like terms: y + -1y = 0 6x + 0 = 3 + -1y 6x = 3 + -1y Divide each side by '6'. x = 0.5 + -0.1666666667y Simplifying x = 0.5 + -0.1666666667y
| 7x+3y-8=4 | | 20w^2-31w+12=0 | | 16a^2-70a+49=0 | | 1x+2=-6 | | -4x^2=9x | | 5a+3(216+a)=888 | | 4y-7-6y-2= | | -2-2(-7x+7)=82 | | -15=-12+3r | | -7(1k-8)+2k= | | 2.5x+4=6x+4 | | 5x+5=6x+2 | | (c+3)(c+4)=2 | | 7x+3=-2x+21 | | Mp+mz=r | | lnx^7-10lnx=1 | | 3+2*[(2+1)*5+8]= | | -5x+2=-2x-31 | | 2y+6+8y+10+y+32=180 | | X^2+13x-64=0 | | 5m-28=-33+6m | | 3x^2+56=-136 | | 9n-23=17+n | | 2y^2-4y-8=y^2+y | | (1.8X+0)-(1.4X+0.6)= | | 2(x+4)-126=0 | | 3+y=10+3 | | m^2+m+.25=0 | | p+12=24 | | (5-4x)(x-5)=0 | | 12x^2-52x+48=0 | | ln(11x-7)=0 |